2009
DOI: 10.1108/19852510980000638
|View full text |Cite
|
Sign up to set email alerts
|

Value Relevance of Book Value and Earnings: Evidence from Two Different Financial Reporting Regimes

Abstract: This study aimed at investigating the value relevance of book value and earnings and the relationship between earnings and operating cash flow of two different financial reporting regimes in Malaysia. A market and nonmarket valuation approaches were utilised for that purpose. The result of market valuation approach of pool sample shows that book values and earnings are value relevant. We also observed that the change in financial reporting regime affects significantly the value relevance of book value and but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…This result implies that the accounting information of earnings and book value are irrelevant and insignificant for the decision-making purposes of foreign investors. The result is in line with Kadri et al (2009), which pointed out that earnings are irrelevant in the Malaysian capital market.…”
Section: Contemporary Management Research 247supporting
confidence: 87%
“…This result implies that the accounting information of earnings and book value are irrelevant and insignificant for the decision-making purposes of foreign investors. The result is in line with Kadri et al (2009), which pointed out that earnings are irrelevant in the Malaysian capital market.…”
Section: Contemporary Management Research 247supporting
confidence: 87%
“…(2019) observed that the impact of IFRS adoption in Brazil is only partial, as their research can find a positive relationship between IFRS adoption and some areas of information quality only. In Malaysia, Kadri et al. (2009) observed that during IFRS adoption, book value per share improved but no change reported on earnings per share.…”
Section: Theory Empirics and Hypothesis Developmentmentioning
confidence: 99%
“…Hasil penelitian menunjukkan hubungan antara book values dan earnings adalah relevan (Kadri, Aziz, & Ibrahim, 2009). Besarnya book values dapat mempengaruhi capital gain suatu saham yang tercermin dari nilai return saham.…”
Section: Rasio Keuanganunclassified